Some Issues Concerning the Bankruptcy Proceedings of the Absent Debtor - Hovhannisyan, Arsen (Bulletin of Yerevan University C: Jurisprudence, 2022)
This article discusses theoretical and practical issues related to the underlying preconditions necessary for initiating the bankruptcy proceedings against an absent debtor, in particular, the subjective frame, the characteristics of the legal entity having effectively terminated its activities, the moment of a decision on recognizing the debtor as an absent debtor, as well as existing legal practice on this issue. The author, in particular, discussed the characteristics of the legal entity having effectively terminated its activities, the theoretical and practical issues related to the decision to consider the debtor absent in the context of the right to fair trial and the goals of the bankruptcy, as well as the applicable legal practice.